Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1186/1471-2350-11-151
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in mannose receptor gene (MRC1) confer susceptibility to increased risk of sarcoidosis

Abstract: BackgroundMannose receptor (MR) is a member of the C-type lectin receptor family involved in pathogen molecular-pattern recognition and thought to be critical in shaping host immune response. The aim of this study was to investigate potential associations of genetic variants in the MRC1 gene with sarcoidosis.MethodsNine single nucleotide polymorphisms (SNPs), encompassing the MRC1 gene, were genotyped in a total of 605 Japanese consisting of 181 sarcoidosis patients and 424 healthy controls.ResultsSuggestive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The MRC1 gene is found on chromosome 10p12 in the vicinity of other genes associated with sarcoidosis and Crohn's disease [66]. A polymorphism of MRC1 with a remarkable odds ratio of 2.53 for sarcoidosis has been identified in a Japanese study, which is, however, also involved in other inflammatory disorders [113]. The extent of serum angiotensin converting enzyme (sACE) increase appears to reflect the total body granuloma load [114].…”
Section: Geneticsmentioning
confidence: 98%
“…The MRC1 gene is found on chromosome 10p12 in the vicinity of other genes associated with sarcoidosis and Crohn's disease [66]. A polymorphism of MRC1 with a remarkable odds ratio of 2.53 for sarcoidosis has been identified in a Japanese study, which is, however, also involved in other inflammatory disorders [113]. The extent of serum angiotensin converting enzyme (sACE) increase appears to reflect the total body granuloma load [114].…”
Section: Geneticsmentioning
confidence: 98%
“…mannose, fucose and N-acetyl-glucosamine (Shepherd et al, 1982). The MR is currently recognized as a prototypic PRR expressed on macrophages, some dendritic cells (Sallusto et al, 1995) and other cell types (Stahl and Ezekowitz, 1998), orchestrating innate and adaptive immune communication (He et al, 2007), and is emerging as a critical regulator of health and disease (Lee et al, 2002; Zhang et al, 2012; Hattori et al, 2010; Hattori et al, 2009). Despite its well-known central role in host recognition of a variety of microbes and ability to modulate inflammatory responses, its receptor-specific role in transducing signals to regulate phagocytosis and inflammatory pathways remains in question (Le Cabec et al, 2005; Gazi and Martinez-Pomares, 2009; Goyal et al, 2016; Hoving et al, 2014; Martinez-Pomares, 2012; Sancho and Reis E Sousa, 2012, Taylor et al, 2005; Gordon, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The MRC1 gene played an active role in innate and adaptive immunity and was naturally proposed to be a candidate gene at the chromosomal region 10p13 that was associated with leprosy (Mira et al 2003;Siddiqui et al 2001). Genetic variants of the MRC1 gene have also been reported to confer susceptibility to increased risk of sarcoidosis (Hattori et al 2010). Despite that we failed to validate the reported association of rs1926736 (p.G396S) of the MRC1 gene with leprosy (Alter et al 2010), we identified two other SNPs in the intron region of this gene that confer a susceptibility to leprosy.…”
Section: Discussionmentioning
confidence: 98%